Environmental impacts of informal economic activities in a low cost housing development, case study of Dunoon, Cape Town - Makabeni, Yonela (Cape Peninsula University of Technology, 2019)
Thesis (Master of Environmental Management)--Cape Peninsula University of Technology, 2018. === Over the past decades, environmental problems associated with low-cost housing developments have been reported on a national and global scale (see Sowman and Urquhart, 1998 and also Norville, 2003). Poor community participation in the early stages of project design and lack of public involvement in decision making regarding low cost housing development are said to have contributed to these environmental issues. The environmental issues that have been reported so far relate to escalating water quality due to poor storm water management and improper waste disposal which poses a threat to the natural environment. While there is as emerging view that the nature of environmental problems experienced in these settlements are due to a lack of participation by local people in decision making, there is virtual no studies that have located this analysis within the theoretical debate of modernist planning. The issue that has been ignored thus far is the fact that low cost housing development (in generally) still resembles the spatial pattern of both the modernist and apartheid planning orthodox. It is thus from this context that the local people are increasingly excluded from participating in decision making. This form of modernist development is contrary to the ethos of sustainable development. In essence, sustainable development, as a new development theory, also adheres to the notion of local citizenry involvement in development for the benefits of the future generation. The research study further argues that poor people need to participate in decision making regarding the design and delivery of these houses (Oelefse, 1997). Therefore, the study investigated the underlying environmental implications associated with informal economic activities in a low cost housing establishment. The research study adopted a qualitative research design and an inductive approach. Dunoon was used as a case study for the research. The study used two sampling techniques, purposive sampling and random sampling,were used. Interviews, questionnaires and observations were used to collect data from the residents, informal businesses in Dunoon and key stakeholders from the Department of Environmnental Affairs as well as City of Cape Town. The findings of the thesis illustrate that long-term environmental impacts that are visible in the low-cost housing development of Dunoon are triggered by informal economic activities that are practised by the local people to make a living. In this regard, this thesis argues that local people need to be involved in the early planning and design stages of low-cost housing development. They need to be involved in all development stages to ensure that they drive the vision of the development. Lack of involvement of the local people in the initial stages of decision-making on the project triggered severe long term environmental impacts. The study then concludes that long-term environmental impacts in Dunoon are intertwined with the escalation of informal economic activities initiated by the local people in order to cope with harsh economic realities. These informal activities are a form of reaction to the imposed version of development. Thus, the environmental problems that emerged out of this pattern of human activities must be analysed by means of conceptualising the Dunoon low-cost housing as a product of modernist planning philosophy. Based on the information gathered and discussed in this thesis, it is concluded that the low-cost housing development is a product of modernist planning.